Flare‐Up After Maxillofacial Surgery in a Patient With Fibrodysplasia Ossificans Progressiva: An [18F]‐NaF PET/CT Study and a Systematic Review. (5th July 2017) - Eekhoff, E Marelise W; Netelenbos, J Coen; de Graaf, Pim; Hoebink, Max; Bravenboer, Nathalie; Micha, Dimitra; Pals, Gerard; de Vries, Teun J; Lammertsma, Adriaan A; Raijmakers, Pieter GHM; van Es, Robert JJ
ABSTRACT: Fibrodysplasia ossificans progressiva (FOP) is a rare genetic disorder leading to progressive heterotopic ossifications (HO) of muscles, tendons, and ligaments, which can be induced by trauma or by surgery. Despite strong medical advice to the contrary, an FOP patient insisted on surgery to alleviate her complete trismus, which caused an unbearable impact on her quality of life (QOL). The entire trismus history of this FOP patient is presented. [ 18 F]‐NaF position emission tomography/computed tomography (PET/CT) scans were introduced as an imaging method for heterotopic bone formation activity. To place our findings into context, a systematic review on jaw surgery in FOP was performed. After falling down the stairs, a 9‐year‐old patient developed mobility impairment of her left‐sided jaw. During the following 13 years bone scintigraphy showed persistent activity of the disease leading to progressive left‐sided zygomatico‐mandibular fusion by HO, resulting in complete trismus. Within 1 month after HO removal on the left side and a matching right coronoidectomy, [ 18 F]‐NaF PET/CT demonstrated a substantial flare‐up activity followed by new HO in both masseter and temporalis muscles. Despite recurrent HO and trismus her QOL increased due to a stable increased interincisal opening of 5.5 mm. Although systematic review reveals a 100% risk of HO recurrence after jaw surgery, information on improved QOL is scarce. In conclusion, surgery in FOP may be beneficial for QOL despite new HO formation. Assessment of disease activity using [ 18 F]‐NaF PET/CT is possible before HO is evident on CT and may serve as a new and quantitative marker of the disease. © 2017 The Authors. JBMR Plus Published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.